Do you want to be my friend? - Carle, Eric (New York : Thomas Y. Crowell, 1987)
"Do you want to be my friend?" asks the lonely little mouse. He follows a tai1, but all he finds at its end is a rather unfriendly horse. The little mouse just wants someone to play with-but he'll have to follow a lot of tails before he can find just the right companion.
Keywords: Stories without words